INFORMATIVE CULTURE AS A FACTOR OF THE DEVELOPMENT OF A PERSONALITY - Кадникова, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article discusses the essence and the role of information culture in shaping the personality in the context of the information society development and the realization of the idea of lifelong education.